Numerical interpretation of the Gurov – Reshetnyak inequality on the real line - Didenko, V. D.; Korenovskii, A. A.; Tuah, N. J. (Ukrains’kyi Matematychnyi Zhurnal, 2016)
We find the “norm” of a power function in the Gurov – Reshetnyak class on the real line. Moreover, as a result of numerical experiments, we establish a lower bound for the norm of the operator of even extension from the semiaxis onto the entire real line in the Gurov – Reshetnyak class.